2016
DOI: 10.1016/j.diagmicrobio.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Helicobacter pylori recovered from gastric biopsies under anaerobic conditions

Abstract: Background and Aim H. pylori can survive long incubation periods under anaerobic conditions, and should be possible to isolate under anaerobic conditions. Our aim was to isolate H. pylori in anaerobic conditions, from gastric biopsies of H. pylori infected patients. Methods We enrolled 27 patients with bleeding (erosive) gastritis (mean age 36.3 years, 55.6% male) from Hanoi, Vietnam. H. pylori status was confirmed by qPCR. Results H. pylori were recovered under anaerobic and micro-aerobic conditions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“… 59 Our results are in accordance with Perez-Perez et al. 39 who reported that two patients out of the eight CagA positive H. pylori isolates lacked the cagA gene.
Fig.
…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“… 59 Our results are in accordance with Perez-Perez et al. 39 who reported that two patients out of the eight CagA positive H. pylori isolates lacked the cagA gene.
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…Of 20 H. pylori strains, 12 (75%) showed the s1/m2 genotype and four showed the s1/m1 genotype. 39 Some of the H. pylori strains showed multiple alleles, despite single colonies being picked. 39
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Concerning culture, the novelty was the possibility to grow H. pylori under anaerobic conditions, which indeed surprisingly yielded significantly higher recovery rates than under microaerobic conditions. 12 Along the same lines, a chemolithoautotrophic growth was described for H. pylori. An H 2 containing atmosphere achieved 40-60% greater growth within 16 h than without H 2 .…”
Section: Methods Based On the Performance Of Endoscopymentioning
confidence: 90%
“…Concerning culture, the novelty was the possibility to grow H. pylori under anaerobic conditions, which indeed surprisingly yielded significantly higher recovery rates than under microaerobic conditions …”
Section: Methods Based On the Performance Of Endoscopymentioning
confidence: 99%